Commentary: Performances of state criticism from the inside. Thoughts on "Contested constructions of trust in the juridical system of Argentina". Issue 3 (2nd September 2018) - Kirsch, Thomas G.
Abstract: This commentary interprets the performance of state criticism by state employees in an Argentinian judicial outreach office as a practice of boundary drawing between state and society that takes place within the 'state system'. It argues that this insight adds complexity to Timothy Mitchell's conceptualization of 'state effects' and that it also contributes to a (pluralized) understanding of state justice and the performative construction of 'the state' as a guarantor of common justice.